Analysis of the success probability of cube attack - Hai-xin SONG; Xiu-bin FAN; Chuan-kun WU; Deng-guo FENG (Tongxin xuebao)
The success probability of cube attack was theoretically discussed when a boolean function was chosen at random and the algebraic degree or the number of terms in its algebraic normal form representation was restricted.The results provided theoretic support to cube attack.The theoretical results meet with the experimental results of the analysis of the stream ciphers Trivium and Grain v1 very closely.